The illocutionary force of laws. Issue 4 (19th May 2018) - Allott, Nicholas; Shaer, Benjamin
Abstract: This article provides a speech act analysis of 'crime-enacting' provisions in criminal statutes, focusing on the illocutionary force of these provisions. These provisions commonly set out not only particular crimes and their characteristics but also their associated penalties. Enactment of a statute brings into force new social facts, typically norms, through the official utterance of linguistic material. These norms are supposed to guide behaviour: they tell us what we must, may, or must not do. Our main claim is that the illocutionary force of such provisions is primarily 'world-creating', i.e. effective, or declarational, rather than directive (behaviour-guiding). We assume that directive illocutionary force is either direct or indirect, showing that provisions need not contain the linguistic items that make for direct directives and that according to standard tests no indirect directive is present. A potential counter-argument is that any utterance serving to direct behaviour is necessarily a directive. We show that this behaviour-directing property is shared by some clear non-directives.